A boy with low-TSH hypothyroidism. Issue 6 (June 1979) - Smail, P J; Isles, T E; Ackroyd, R S
Abstract : A case of long-standing mild hypothyroidism is described. This was caused by partial TSH deficiency probably of hypothalamic origin, with no other pituitary hormone deficiencies, although with a decreased response of FSH and LH to LHRH.